ANALISIS FAKTOR PENYEBAB DAN STRATEGI PENGENDALIAAN KEKERINGAN DANAU AYAMARU KABUPATEN MAYBRAT - Jembris Smur; Dewi Ana Rusim; Janviter Manalu (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2021)
Drought is a natural event and attacks slowly, such as the drought that occurred in Lake Ayamaru which has had a very wide adverse impact on people in Maybrat Regency, because the function of the lake has been lost in recent years. Considering that drought is a recurring event, it is necessary to know the causes of drought and control strategies, so that the aim of this study is to conduct an analysis to determine the factors causing drought in Ayamaru Lake and the efforts made to control drought, so that it can be used as a reference to minimize the drought that occurs. The research method used is descriptive qualitative and quantitative research. The data sources used are primary and secondary data. Data collection techniques using questionnaires, in-depth interviews (indepth interview), documentation and direct observation. The data used, namely, the data that was filtered through the results of the questionnaire, was processed and analyzed by the qualitative-quantitative descriptive method using the cross tabulation approach (crosstabulation). The data collected is categorized using a Likert scale. This shows that the cause of the dryness of Lake Ayamaru is due to Rock properties factors, Rainfall factor, Topographic factors, Land use factors; and control strategies implemented to overcome drought, namely; The vegetative method is carried out with reforestation and agroforestry. The mechanical method is by constructing a sediment control building (check dam) and making a triangular terrace on the slope area.